Role of Information and Communication Technologies on Tourism: Nepal Case Study - Kharel, Sameer (Nepalese Journal of Management Science and Research, 2024)
Nepal’s natural beauty and the Himalayas make it a well-liked tourism destination. The GDP of the country is heavily impacted by the tourism sector. Information and communication technology (ICT) is an efficient instrument for boosting the travel and tourism sector. The Nepalese government intends to fully digitize this industry as well. The goal of this research was to examine ICT use in Nepalese tourism sector. For the research, a thorough study of the literature was done along with interviews. Social media was discovered to be beneficial to the sector. According to the study, ICT use in tourism sector is proceeding per the Digital Nepal Framework (DNF), however, the speed of implementation appears to be slow and the full adoption of Industry 4.0 appears to be far off from the current situation.